ChemInform Abstract: Electrophilic Trifluoromethylation of Carbonyl Compounds and Their Nitrogen Derivatives under Copper Catalysis. Issue 10 (February 2016) - Prieto, Alexis; Baudoin, Olivier; Bouyssi, Didier; Monteiro, Nuno
Abstract: Review: [45 refs.